Keynes, Sraffa et l’économie classique : le problème de la mesure de la valeur - Seccareccia, Mario (L'Actualité économique)

(untitled) (HEC Montréal, 1982)
AbstractThe author traces the various stages in the development of a viable measure of the net product. Beginning with Petty's seminal exposition of the problem, the paper then analyzes the Physiocratic fixed-price composite-commodity measure, the Smith-Keynes 'labour command' approach, and the Ricardo-Sraffa 'standard commodity' method of defining the net product. Although being the most accurate of the various techniques, the author concludes that Sraffa's method did not solve all the measurement problems raised by the classical economists.